RELIGIOUS AND MULTICULTURAL EDUCATION: INTRODUCING INTERFAITH DIALOGUE IN THE INDONESIAN EDUCATIONAL SYSTEM - Nina Mariani Noor; Ferry Muhammadsyah Siregar (Al-Albab, 2013)
Religious education which is taught in schools has a significant role in forming religious exclusivism and inclusivism, especially in Indonesia. It influences student’s views on others. It also depends on the way those religion educations taught. There is also a need to have more efforts to bring the idea of interfaith dialogue into educational system including in higher educational level. There are some educational institutions which already involved in inter-faith dialogue in their curriculum such as the CRCS (Center for Religious and Cross Cultural Studies) and the ICRS (Indonesian Consortium for Religious Studies) at Gadjah Mada University. However, the number of primary educational institutions which involves interfaith dialogue is still limited. This work suggests that, for today’s situation in Indonesian multicultural society, a need for reforming religion education curriculum in primary education is emerging. To make interfaith dialogue real in schools, the Ministry of Education in collaboration with Ministry of Religious Affairs is in a front line to arrange a new curriculum on religious education to be more pluralistic and affirm religious diversity in Indonesia including multi-religious education or inter religious education. Key words: religious, multicultural, education, interfaith.